2020
DOI: 10.1016/j.ultrasmedbio.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal VEGF-Targeted Contrast-Enhanced Ultrasound and Photoacoustic Imaging of Rats with Inflammatory Arthritis: Using Dye-VEGF-Antibody-Loaded Microbubbles

Abstract: Owing to the heavy health burdens from rheumatoid arthritis, a sensitive and objective imaging method is needed for early diagnosis and accurate evaluation of the disease. We aimed to fabricate vascular epithelial growth factor (VEGF)Àtargeted microbubbles (MBs) to evaluate the expression levels of VEGF within the inflammatory lesions of rats with adjuvant-induced arthritis (AIA) using a multimodal photoacoustic (PA)/ ultrasound (US) imaging system. Fluorescein isothiocyanateÀbiotin double-labeled vascular end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
(28 reference statements)
0
10
0
Order By: Relevance
“… 274 Hence, efforts have been made to combine micro/nanobubbles with optical agents, so they can be used for dual-modal US/PA imaging. 261 , 275 For example, Zhao et al. 275 reported a dual-modal contrast agent that was composed of microbubbles loaded with vascular epithelial growth factor (VEGF) antibodies and fluorescent dyes.…”
Section: Multimodal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“… 274 Hence, efforts have been made to combine micro/nanobubbles with optical agents, so they can be used for dual-modal US/PA imaging. 261 , 275 For example, Zhao et al. 275 reported a dual-modal contrast agent that was composed of microbubbles loaded with vascular epithelial growth factor (VEGF) antibodies and fluorescent dyes.…”
Section: Multimodal Imagingmentioning
confidence: 99%
“… 261 , 275 For example, Zhao et al. 275 reported a dual-modal contrast agent that was composed of microbubbles loaded with vascular epithelial growth factor (VEGF) antibodies and fluorescent dyes. As the expression level of VEGF in the synovial tissues of rheumatoid arthritis (RA) patients is very high, VEGF can be regarded as a specific biomarker for the RA disease.…”
Section: Multimodal Imagingmentioning
confidence: 99%
“…Nanobubbles can skip normal cells and expand the intracellular internalisation of the medication by the tumour cells. Likewise, they have an extra advantage of allowing imaging of the tumour by ultrasound techniques [49]. A successful trial for nanobubbles being used as carriers for doxorubicin as an anticancer drug on the basis of in vitro and in vivo studies was reported by Rapaport et al [50].…”
Section: Nanobubblesmentioning
confidence: 99%
“…Similarly, Fournelle et al used an antitumor necrosis factor-α (TNF-α) antibody-coupled to gold nanorods as nanoprobes for confirming the overexpression of TNF-α in arthritic knees [ 87 ]. Instead of using nanoparticles, dye-VEGF-antibody-loaded microbubbles enabled multimodal OAI and US imaging of rats with inflammatory arthritis [ 88 ].…”
Section: Optoacoustic Imaging Of Inflammation: Applicationsmentioning
confidence: 99%